Revitalizing Regional Languages to Support Sustainable Development Goals from a Collaborative Governance Perspective - Puspitasari, Putri Ayu; Subanda, I Nyoman (Dinasti Research, 2024)
The revitalization of regional languages has become a strategic issue in preserving cultural identity while supporting the achievement of the Sustainable Development Goals (SDGs), particularly Goal 4 (quality education), Goal 11 (sustainable cities and communities), and Goal 16 (peaceful and inclusive societies). This study aims to analyze how collaborative governance practices can strengthen regional language revitalization programs as an integral part of sustainable development. The method used is descriptive qualitative with a literature study and policy analysis approach, focusing on the roles of cross-sector actors such as local governments, indigenous communities, educational institutions, and civil society organizations. The results show that the success of regional language revitalization is largely determined by the level of participation and synergy among stakeholders. The collaborative governance model provides a framework that facilitates dialogue, coordination, and sustainable collaboration in the planning and implementation of language policies. Therefore, the revitalization of regional languages is not only a cultural preservation agenda but also a meaningful contribution to inclusive and sustainable development.